PENGARUH MANAJEMEN KINERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PT. PELABUHAN INDONESIA I (PERSERO) CABANG DUMAI - Kuswara Anghea Kenny; Nuryanti Nuryanti; Rifqi Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of performance management andcompetence on employee performance through work motivation as an interveningvariable at PT. Pelabuhan Indonesia I (Persero) Dumai Branch. The populationin this study includes all employees at PT. Pelabuhan Indonesia I (Persero)Dumai Branch, totaling 119 people. Primary data was collected using aquestionnaire as an instrument to prove the results of the study, to test thehypothesis in this study, path analysis was used with the help of SPSS version 26software. The sampling technique used was Proportionate Stratifed RandomSampling or dividing the population into sub-populations/strata proportionallyand carried out randomly (119 employees at PT. Pelabuhan Indonesia I (Persero)Dumai Branch). The results of this study indicate that: 1) PerformanceManagement has a positive and significant effect on Work Motivation, 2)Competence has a positive and significant effect on Work Motivation, 3)Performance Management has a positive and significant effect on EmployeePerformance, 4) Competence has a positive and significant effect on PerformanceEmployees, 5) Work Motivation has a positive and significant effect on EmployeePerformance, 6) Performance Management has a positive and significant effecton Employee Performance through Work Motivation, 7) Competence has apositive and significant effect on Employee Performance through WorkMotivation. Keywords: Performance Management, Competence, Work Motivation, EmployeePerformance